Density Dependent Refueling of Migratory Songbirds During Stopover Within an Urbanizing Coastal Landscape - Cohen, Emily B.; Lafleur, Jill M.; Moore, Frank R. (Frontiers in Ecology and Evolution, 2022)
Refueling performance is the primary currency of a successful migration as birds must maintain energy stores to achieve an optimal travel schedule. Migrating birds can anticipate heightened energy demand, not to mention increased uncertainty that energy demands will be satisfied, especially within an urbanizing landscape following long-distance flights. We tested the expectation that refueling performance of songbirds is reduced as densities increase at stopover sites in an urbanizing coastline of the Gulf of Mexico. We measured the density of migrating birds, their refueling performance, and arthropod abundance in two large tracts of contiguous forest paired with two small isolated patches embedded within residential settings throughout spring migration over the course of two years. Refueling performance declined with increasing migrant densities, even though the overall daily densities of birds stopping in these landscapes were relatively low and arthropod densities were low throughout. Habitat patch size alone did not account for differences in refueling performance, but smaller habitat patches more often concentrated migrants in higher densities where they experienced reduced refueling performance. We found support for density-dependent refueling performance during spring migration through a region where overall passage and stopover densities are low; suggesting that larger contiguous forest tracks within urban landscapes provide higher quality habitat for refueling and that effect is likely even more pronounced in landscapes within higher density migratory corridors. The nutritional challenges encountered during migration influence the overall pace of migration and changes in access to food resources due to increasing urbanization may ultimately impact optimal travel schedules.